Be more Cat - Davey, Seb; Lamb, Eleanor; Shutterstock.com (New York, NY : BOXER BOOKS Ltd., 2024)
Tapping into the mindfulness movement, this fun and positive board book explores the ways we can "be more cat" and embrace the positive things in life. From playing outside and feeling the sunshine on our face to slowing down and watching the world go by, this is a delightful package that will be enjoyed by parents/carergivers and children alike.
On board pages.
Keywords: Mindfulness (Psychology) -- Juvenile fiction; Emotions -- Juvenile fiction; Self-help techniques -- Juvenile fiction; Positive psychology -- Juvenile fiction; Cat -- Children's picture books; Board books